Connected Health in Hypertension Management - Omboni, Stefano (Frontiers in Cardiovascular Medicine, 2019)
The use of electronic processes and communication technologies to provide more efficient healthcare services and improve the quality of care is defined as e-health. Among all the possible e-health services the most popular and widely distributed among healthcare professionals and the general public are those based on telemedicine and mobile health (m-health). These applications allow the exchange of medical information from one site to another, mainly through the Internet, and are used to provide healthcare services remotely (so-called “connected health”). The most popular telemedicine application for hypertension management is blood pressure telemonitoring (BPT), which allows remote data transmission of BP and additional information on patients’ health status from their dwellings or from a community setting to the doctor’s office or the hospital. There is sufficiently strong evidence from several randomized controlled trials that the regular and prolonged use of BPT combined with telecounseling and case management under a supervision of a team of healthcare professionals, including a community pharmacist (so-called telepharmacy), is associated with a significant BP reduction and with antihypertensive medication intensification and optimization compared to usual care. The major benefits of BPT are usually observed in high-risk patients. BPT can also be provided in the context of m-health wireless solutions, together with educational support, medication reminders and teleconsultation. In this context, BPT has the potential to promote patient’s self-management, as a complement to the doctor’s intervention, and encourage greater participation in medical decision making, with consequent improvement in BP control and medication adherence. Thus, according to current evidence, e-health solutions, and in particular telemedicine, are progressively gaining a key role in the management of hypertensive patients, having the potential to improve the quality of the delivered care and to more effectively control BP and prevent the cardiovascular consequences of arterial hypertension.